A (re)organização da produção: um estudo da segurança alimentar nos assentamentos de reforma agrária Santa Rita e Sepé Tiarajú, município de Capão do Cipó (RS) - Silva, Tanise Pedron da (2012)
The power in the countryside passes by recent transformations in the social reproduction of the family is marked by instabilities generated by the negligence of certain practices common to agriculture labor predominantly family. This dissertation aims to identify the possible reasons that limit farmers to be included in your organization productive food security strategies, and to characterize any potential likely to re-establish any food security strategies. To elaborate this thesis, there was first a theoretical study to analyze the internal logic of rural households, demonstrating that the security of supply is intrinsic to the lifestyle of those in rural areas, forming what we call here the essence of farmer ensuring the social reproduction of families. In this theoretical study, we performed a historical review of the different conceptions that food safety has taken over time, analyzing how to incorporate the discourse of capitalist development reaches the power to observe and decide to farmers at the ecosystem, and consequently, achieving a form of organization of production. That same perspective is also analyzed the proximity of the rural with the urban environment, trying to understand the extent to which rural households re-determine its priorities as a result of assimilation of the particularities of the urban environment. From this theoretical effort, we decided to empirical work, adopting the agrarian reform Santa Rita and Sepé Tiarajú, located in the town of Capão do Cipó (RS), through semi-structured interviews with families seeking to demarcate key their similarities and differences regarding the organization of production. Overall, the results pointed to a process in which the settlers in the search for following the guidelines for adoption of technologies in line with capitalist development, have contributed to breaking this particular way of life. Added to this fact, it is emphasized that most young people these settlements are opting out of the countryside taking jobs in urban areas, for purposes of seeking an independent income from agriculture work without commitment to the perpetuation of the family on the lot. Starting from the idea that the organization of production reflects the priorities listed by the family, you can see that the changes in household arising from the neglect of food safety practices, which is bound either by disruption of the farmer as the essence of each line increasing with specificities of the urban environment.